AN ANALYSIS ON CONNOTATIVE MEANING AND MESSAGE IN LINKIN PARK’S SONGS IN A THOUSAND SUNS ALBUM - PRAYITNA, NADIA APRILIA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords : semantics, connotative meaning, song lyrics, Linkin Park and A Thousand Suns album Language is a fundamental device used by people to communicate. A sentence or an utterance in which people use to express their feelings and thoughts is generally containing either literal meaning or non-literal meaning. One kind of non-literal meaning is connotative meaning which is subjective and not perceived the same way by the speakers of a language. This research focuses on analysing the connotative meaning contained in Linkin Park’s song lyrics by using Leech’s theory (1990). This research is aimed to show the interpretation of the connotations found in the song lyrics, the messages of the songs, and the contribution of the connotations to the messages. The problems of the study are (1) what are the expressions containing connotative meanings in the song lyrics of Linkin Park’s A Thousand Suns album, (2) what are the messages of the songs in Linkin Park’s A Thousand Suns album, and (3) how do the connotations contribute to the messages conveyed in the songs. This research used qualitative approach because the data are in the form of song lyrics. Documentary analysis was applied to find out the connotative meaning contained in the song lyrics, the messages, and the contribution of the connotations to the messages of the songs. The researcher collected the data by downloading the songs and the lyrics, reading the song lyrics, and making a list of the expressions that contain connotative meaning. Then the researcher analyzed the data by identifying the connotative meanings, figuring out the messages, and correlating the contribution of the connotations to the messages. The result of the research shows that there are 46 utterances containing connotative meanings in the song lyrics. The connotative meaning found is carried within words, phrases, and also sentences. The messages conveyed in the songs are mostly motivating and persuasive. The connotations used in the song lyrics are to portray images and build certain atmospheres. The connotations found in the song lyrics play an important role in creating particular senses and delivering the messages.The researcher suggests the next researchers conduct a research in semantics field by using different object of the study such as Indonesian songs. Also, different theory may be used as well in order to get more understanding about connotative meaning.